2016
DOI: 10.1021/acs.jafc.6b00274
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Nigella sativa L. to Zinc Excess: Focus on Germination, Growth, Yield and Yield Components, Lipid and Terpene Metabolism, and Total Phenolics and Antioxidant Activities

Abstract: A comprehensive analysis of the responses of Nigella sativa L. to elevated zinc concentrations was assessed in pot experiments. Zn excess supply did not affect the germination but drastically reduced radicle elongation. A concentration-dependent reduction in all growth parameters, yield, and yield components was observed. With the increasing Zn concentrations, total lipid contents decreased and changes in fatty composition toward the production of saturated ones were underscored. Despite the reduction in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 54 publications
5
19
1
Order By: Relevance
“…Our results also showed a dramatically reduction in carotenoid contents in response to Zn excess as compared to other photosynthetic pigments. In addition, the significant decrease in chlorophyll contents (total chlorophyll (Chla + Chlb), Chla, and Chlb) seems to be more pronounced in Chlb than Chla, which is similar to the results of Marichali et al (2016) who reported that the content of photosynthetic pigments of Nigella sativum was significantly reduced as well as Chlb content, being this pigment more sensitive to Zn excess than Chla.…”
Section: Results Depicted Insupporting
confidence: 89%
See 1 more Smart Citation
“…Our results also showed a dramatically reduction in carotenoid contents in response to Zn excess as compared to other photosynthetic pigments. In addition, the significant decrease in chlorophyll contents (total chlorophyll (Chla + Chlb), Chla, and Chlb) seems to be more pronounced in Chlb than Chla, which is similar to the results of Marichali et al (2016) who reported that the content of photosynthetic pigments of Nigella sativum was significantly reduced as well as Chlb content, being this pigment more sensitive to Zn excess than Chla.…”
Section: Results Depicted Insupporting
confidence: 89%
“…High amounts of zinc accumulated in plants leads to the induction of oxidative stress and, consequently, to the alteration of their physiological processes, according to the investigation made in model plants. Nevertheless this sort of research, using medicinal and aromatic plants is scarce (Marichali et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such results might be unexpected because Zn is considered to possess antioxidant property, since it works as a co-factor of some antioxidant defense enzymes (Marreiro et al, 2017). However, Ajina et al (2017) reported that Zn provided to infertile men with asthenozoospermia and asthenoteratozoospermia did not prevent sperm lipid peroxidation or more recently, some authors (Lee, 2018;Marichali et al, 2016) described that an excess of Zn may cause oxidative stress evidenced by increased lipid peroxidation products (MDA) due to its pro-oxidant activity leading to cellular death.…”
Section: Antioxidant and Anti-inflammatory Activitiesmentioning
confidence: 99%
“…On fact, the amounts of Zn consumed and its bioavailability can affect its intestinal absorption (Wang et al, 2015). Zn excess affects membrane integrity and permeability and induces oxidative stress via the generation of reactive oxygen species (RDS) which promotes the peroxidation of lipids (Marichali et al, 2016). Ot has been also reported that Zn toxicity reduces the survival rate of Escherichia coli, despite the proved role of Zn for microbes and other cell growth (Babich & Stotzky, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the added nutrients effect on SDG depended mainly on either irrigation or fertilization treatments supporting their little contribution (3.17%, p ˂ 0.01, Table 2) to SDG variation under this trial. This can also be ascribed to that both humic acids and zinc applications can significantly increase phenolic compounds (Marichali et al, 2016, Schiavon et al, 2010, Song et al, 2015, but their interactions with other agronomical treatments may result in variations in phenolic contents.…”
Section: Effect Of Fertilization On Sdg Content and Yieldmentioning
confidence: 99%